Polyvinyl Chloride Microplastic Exposure Alters Body Colour and Reduces Condition Factor in Guppy (Poecilia reticulata) - Rifki Rijal Hapriawan; Bagus Dwi Hari Setyono; Muhammad Sumsanto (Journal of Fish Health, 2026)
Polyvinyl chloride (PVC) microplastics may compromise fish health, but visible sublethal responses in ornamental fish remain poorly documented. This study evaluated whether nominal PVC microplastic exposure altered CIE L*a*b* body-colour indices, Fulton's condition factor, and survival of guppy (Poecilia reticulata). A completely randomized design included 0, 5, 15, and 20 mg/L PVC treatments, each with three aquaria stocked with 10 fish and maintained for 45 days. Treatment means were evaluated by one-way analysis of variance and Duncan's multiple range test. The 15 and 20 mg/L treatments produced higher lightness and lower redness and yellowness than the control and 5 mg/L treatments. At 20 mg/L, survival declined to 66.67 ± 15.28% and the condition factor declined to 0.96 ± 0.13. These results show a marked fading of red and yellow body-colour components at 15 to 20 mg/L, while reduced survival and condition factor were most evident at 20 mg/L. Digital CIE L*a*b* metrics may therefore provide a practical visual endpoint for screening sublethal responses of ornamental fish to nominal PVC microplastic exposure. The study did not test the physiological mechanisms that generated the colour response.